Marital Dissatisfaction and Depression: A Comparative study among Infertile Couples of Punjab - Babar Javaid, Rahila Ajmal, Umaima Ahmad, Azra Abdul Rashed, Aujalla Babur Khan, Hifsa Batool, Farah Zainab, Anila Safdar, (Pakistan Journal of Medical & Health Sciences, 2022)
Although most studies on the effects of infertility-related stress focus on individuals, there has been little study on how marital dissatisfaction and co morbid feelings are connected with each other and affect infertile couples. The current study intended to analyze level of marital dissatisfaction and depression among infertile couples. Index of marital satisfaction (IMS) for measuring marital satisfaction and Beck depression inventory (BDI) for measuring depression was used as tool of study.1 The sample of 200 married couples were included 100 couples were fertile and 100 couples were infertile. The results indicated that infertile couples are more martially dissatisfied. Female are more martially dissatisfied. The findings of this study also indicted that there is a positive relationship between marital dissatisfaction and depression among the infertile couples.2 Keywords: Marital dissatisfaction, depression, infertile couples, Punjab